Herbal Antibiogram and Antisporulation: In Vitro Assessment on Bacterial Isolates and Eimeria oocysts from Rural Poultry in South Andaman - Tamilvanan, Sujatha; Sunder, Jai; Kumeresan, Abirami; Samaddar, Gayathri; Raju, Mayuri; Bhowmick, Sneha (International Journal of Livestock Research, 2020)
In-vitro work was designed to determine antimicrobial and anti-sporulation effect of Zingiber spectabile, Piper betle, Cissus quadrangularis, Costuspictus and Centella asiatica extracts on cloacal isolates and Eimeria oocysts from Vanaraja birds. Antibiogram in terms of zone of inhibition (ZI) of methanolic extracts of herbal extracts at concentrations (µg) against salmonella and E. coli isolates were performed. The percentage of sporulation inhibition (SI) of herbal extracts was estimated on oocysts collected from naturally coccidiosis infected birds. Extracts of Zingeber spectabile (510 µg) and Piper betle (557 µg) exhibited significantly highest antibacterial activity (15.92 mm) against E. coli isolates and against the Salmonella isolates it was 16.6 mm with Zingeber spectabile (587 µg) and Piper betle (534 µg). The extracts of Zingiber spectabile(root) and Piperbbetle (leaf) inhibited sporulation of oocysts significantly higher (>80%). The anti-bacterial properties and pronounced anti-sporulation activity on oocysts of methanolic extracts of these medicinal plants have revealed that they could be further studied and explored for feed and water supplements as anti-coccidial in poultry.